RICA 2020
DOI: 10.20937/rica.53495
|View full text |Cite
|
Sign up to set email alerts
|

Alteraciones Del Ciclo Menstrual De Adolescentes Expuestas No Ocupacionalmente a Una Mezcla De Plaguicidas De Una Zona Agrícola De San Luis Potosí, México. Estudio Piloto

Abstract: Persistent organic pollutants are a group of chemical compounds of global concern due to the health damages caused by the exposure to them. Their capacity as endocrine disrupters is one of their main characteristics, being women in reproductive age the most vulnerable population. The aim of the present study was to evaluate the effect of exposure to a mixture of pesticides in the menstrual cycle of a sample of 29 teenagers between the ages of 12 and 17 years old from El Refugio, San Luis Potosi, Mexico, a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Descriptive data (a) Give characteristics of study participants (e.g. demographic, clinical, social) and information on exposures and potential confounders Regarding the quality of evidence, seven studies (35,36,37,38,39,40,41) were classified as 'very low', five (42,43,44,45,46) as 'low', and one (47) as 'moderate'. The main reasons for downgrading the quality were risk of bias due to inadequate control of plausible confounders and imprecision due to the small sample size.…”
Section: Study Sizementioning
confidence: 99%
See 4 more Smart Citations
“…Descriptive data (a) Give characteristics of study participants (e.g. demographic, clinical, social) and information on exposures and potential confounders Regarding the quality of evidence, seven studies (35,36,37,38,39,40,41) were classified as 'very low', five (42,43,44,45,46) as 'low', and one (47) as 'moderate'. The main reasons for downgrading the quality were risk of bias due to inadequate control of plausible confounders and imprecision due to the small sample size.…”
Section: Study Sizementioning
confidence: 99%
“…In the same line, Croes et al (45) found that higher urinary levels of OP metabolites diethylphosphate (DEP), diethylthiophosphate (DETP), and diethyl dithiophosphate (DEDTP) were associated with lower Tanner breast stage at the age of 14-15 years. Furthermore, Rodríguez-López et al (41) found higher urinary dimethylphosphate (DMP) and DEDTP levels in girls with alterations in serum LH levels, and Graham et al (35) observed increased age at menarche in girls living in farming areas environmentally exposed to non-endocrine-disrupting pesticides in comparison to non-exposed girls. In other studies, Suh et al (40) found no difference in the urinary levels of 320 compounds (including non-persistent pesticide metabolites) between 30 girls experiencing precocious puberty and 30 prepubertal controls, while Guillette et al (37) found no difference in breast Tanner stage between peripubescent girls living in agricultural vs non-agricultural areas.…”
Section: Study Sizementioning
confidence: 99%
See 3 more Smart Citations